Brazil and COVID-19: Challenges of Remote Education in Basic Education - Martins da Silva Andrea (International Journal of Coronaviruses, 2020)
A commentary on remote education challenges during COVID‑19 in Brazil. It covers equity, infrastructure, teacher training, and student engagement, proposing pragmatic steps to support learning continuity.
Keywords: Coronavirus